Investigating the efficacy of PVDF membranes customized with sulfonated graphene oxide nanosheets for enhanced permeability and antifouling. Issue 5 (October 2020) - Sri Abirami Saraswathi, Meenakshi Sundaram; Rana, Dipak; Kaleekkal, Noel Jacob; Divya, Kumar; Nagendran, Alagumalai
Graphical abstract: Highlights: Highly permeable PVDF/SGO nanocomposite UF membranes were fabricated by phase inversion technique. PVDF-2 membrane showed improvement in 246% of pure water flux in comparison with the neat PVDF membrane. SGO enhanced the PVDF membrane's hydrophilicity and long-term stability. PVDF/SGO membranes showed a 98% rejection of bovine serum albumin and humic acid. SGOimparts higher antifouling character to the PVDF UF membranes. Abstract: Poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes are fabricated using the incorporation of sulfonated graphene oxide (SGO) nanosheets with the aim of enhanced separation of biomacromolecular protein and natural organic matter. The effect of the addition of SGO on the PVDF membrane is evaluated with specific emphasis on morphology, surface hydrophilicity, pure water flux (PWF), bovine serum albumin (BSA) and humic acid (HA) separation. The experimental results revealed that the PVDF membrane with 2 wt.% SGO exhibited the enhanced PWF of 155.5 Lm -2 h -1 and more than 98% of BSA and HA rejection due to its improved hydrophilicity and more porous morphology. The antifouling ability of the PVDF membranes is improved to a great extent with the incorporation of SGO nanosheets is confirmed by the greater than 95% of flux recovery ratio during the filtration of BSA and HA. SGO inherits useful functional groups from graphene oxide and possesses better miscibility with the incorporated polymer matrix due to the presence of strongly charged -SO 3- units which is attributed to the relatively enhanced hydrophilicity of the modified membranes. Especially, SGO has extensively employed in membrane-based water treatment as SGO promotes better water permeability performances, together with adequate resistance towards hydraulic pressure. In view of these entire outcomes, it is apparent that the SGO incorporated PVDF nanocomposite UF membrane proves the potential for water and wastewater treatment applications.